Pendekatan Antropologi dalam Studi Islam: Kajian Terhadap Peran Sosial-Budaya Lembaga Pendidikan Dayah di Aceh - Mujlisal (Jurnal Keislaman, 2025)
The emergence of Dayah in Aceh as an educational institution has been going on for several centuries. Historical records show that at the beginning of its presence as a laboratory for producing preachers in the spread of Islam, it has changed into producing preachers who have become a stronghold of the socio-cultural defence of the Acehnese people, who are thick with Islamic law values. Historians' records show that the existence of Dayah as an educational institution in Aceh has experienced various phases, including the emergence phase, the golden phase, the decline phase, and now the modernisation phase. In this study, the author wants to see how the socio-cultural role of educational institutions that have experienced various phases in the history of Aceh. The author uses a qualitative approach with ethnographic methods to reveal the socio-cultural role played by Dayah educational institutions in Acehnese society. The results of the study indicate that Dayah educational institutions in Aceh play a crucial role in guiding the socio-cultural development of the region. As in the social life of the community, Tengku alumni of Dayah are entrusted to become imam meunasah, imum mukim, and even several other strategic positions.